2018
DOI: 10.1002/chem.201804151
|View full text |Cite
|
Sign up to set email alerts
|

Modular Enzymatic Cascade Synthesis of Vitamin B5 and Its Derivatives

Abstract: Access to vitamin B [(R)-pantothenic acid] and both diastereoisomers of α-methyl-substituted vitamin B [(R)- and (S)-3-((R)-2,4-dihydroxy-3,3-dimethylbutanamido)-2-methylpropanoic acid] was achieved using a modular three-step biocatalytic cascade involving 3-methylaspartate ammonia lyase (MAL), aspartate-α-decarboxylase (ADC), β-methylaspartate-α-decarboxylase (CrpG) or glutamate decarboxylase (GAD), and pantothenate synthetase (PS) enzymes. Starting from simple non-chiral dicarboxylic acids (either fumaric ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 31 publications
(53 reference statements)
1
16
0
Order By: Relevance
“…[46] Moreover, MAL and its H194 A variant were used to form linear cascades of three different enzymes in one pot to build an in vitro artificial pantothenate biosynthesis pathway for the production of vitamin B 5 [(R)-pantothenic acid] and its derivatives ( Figure 7). [47] Vitamin B 5 is the biosynthetic precursor of coenzyme A, and its derivatives serve as important synthetic precursors to antimicrobial pantothenamides. A one-pot, threestep enzymatic cascade was developed, consisting of asymmetric hydroamination (catalyzed by MAL or MAL-H194A), αdecarboxylation (catalyzed by an appropriate decarboxylase) and condensation (catalyzed by pantothenate synthase) reactions.…”
Section: Synthetic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[46] Moreover, MAL and its H194 A variant were used to form linear cascades of three different enzymes in one pot to build an in vitro artificial pantothenate biosynthesis pathway for the production of vitamin B 5 [(R)-pantothenic acid] and its derivatives ( Figure 7). [47] Vitamin B 5 is the biosynthetic precursor of coenzyme A, and its derivatives serve as important synthetic precursors to antimicrobial pantothenamides. A one-pot, threestep enzymatic cascade was developed, consisting of asymmetric hydroamination (catalyzed by MAL or MAL-H194A), αdecarboxylation (catalyzed by an appropriate decarboxylase) and condensation (catalyzed by pantothenate synthase) reactions.…”
Section: Synthetic Applicationsmentioning
confidence: 99%
“…Moreover, MAL and its H194 A variant were used to form linear cascades of three different enzymes in one pot to build an in vitro artificial pantothenate biosynthesis pathway for the production of vitamin B 5 [( R )‐pantothenic acid] and its derivatives (Figure ) . Vitamin B 5 is the biosynthetic precursor of coenzyme A, and its derivatives serve as important synthetic precursors to antimicrobial pantothenamides.…”
Section: Methylaspartate Ammonia Lyase (Mal)mentioning
confidence: 99%
“…Recently, we reported that pantothenate synthetase from Escherichia coli (PS E. coli ) was able to accept both the (R)-and (S)-enantiomers of α-methyl-substituted β-alanine (3-amino-2-methylpropanoic acid) as nonnative amine substrates for coupling to 1. 25 This substrate promiscuity was exploited for the enzymatic cascade synthesis of both diastereoisomers of α-methyl-substituted pantothenic acid…”
Section: Introductionmentioning
confidence: 99%
“…A remarkable class of promising antimicrobials that target CoA biosynthesis is constituted by pantothenamides, which are secondary or tertiary amides of pantothenic acid. They acquire effective antimicrobial activity against many micro‐organisms including the pathogenic bacterium Staphylococcus aureus and the malaria parasite Plasmodium falciparum (Abidin et al, ; Spry et al, ). The action of VB5 is controlled by pantetheinase enzymes that normally hydrolyze pantetheine and in human serum also act on the pantothenamides, thereby reducing their efficacy (Abidin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…They acquire effective antimicrobial activity against many micro‐organisms including the pathogenic bacterium Staphylococcus aureus and the malaria parasite Plasmodium falciparum (Abidin et al, ; Spry et al, ). The action of VB5 is controlled by pantetheinase enzymes that normally hydrolyze pantetheine and in human serum also act on the pantothenamides, thereby reducing their efficacy (Abidin et al, ). Furthermore, the vascular noninflammatory (vanin) molecules are enzymes that convert pantetheine to pantothenic acid (VB5).…”
Section: Introductionmentioning
confidence: 99%